Ketogenic diet treatment of defects in the mitochondrial malate aspartate shuttle and pyruvate carrier - Bölsterli Heinzle, Bigna; Boltshauser, Eugen; Palmieri, Luigi; Spenger, Johannes; Brunner-Krainz, Michaela; Distelmaier, Felix; Freisinger, Peter; Geis, Tobias; Gropman, Andrea L.; Häberle, Johannes; Hentschel, Julia; Jeandidier, Bruno; et al. (Nutrients, 2022)
The mitochondrial malate aspartate shuttle system (MAS) maintains the cytosolic NAD+/NADH redox balance, thereby sustaining cytosolic redox-dependent pathways, such as glycolysis and serine biosynthesis. Human disease has been associated with defects in four MAS-proteins (encoded by MDH1, MDH2, GOT2, SLC25A12) sharing a neurological/epileptic phenotype, as well as citrin deficiency (SLC25A13) with a complex hepatopathic-neuropsychiatric phenotype. Ketogenic diets (KD) are high-fat/low-carbohydrate diets, which decrease glycolysis thus bypassing the mentioned defects. The same holds for mitochondrial pyruvate carrier (MPC) 1 deficiency, which also presents neurological deficits. We here describe 40 (18 previously unreported) subjects with MAS-/MPC1-defects (32 neurological phenotypes, eight citrin deficiency), describe and discuss their phenotypes and genotypes (presenting 12 novel variants), and the efficacy of KD. Of 13 MAS/MPC1-individuals with a neurological phenotype treated with KD, 11 experienced benefits—mainly a striking effect against seizures. Two individuals with citrin deficiency deceased before the correct diagnosis was established, presumably due to high-carbohydrate treatment. Six citrin-deficient individuals received a carbohydrate-restricted/fat-enriched diet and showed normalisation of laboratory values/hepatopathy as well as age-adequate thriving. We conclude that patients with MAS-/MPC1-defects are amenable to dietary intervention and that early (genetic) diagnosis is key for initiation of proper treatment and can even be lifesaving.